COGNITIVE AND AFFECTIVE DIMENSIONS OF FOREIGN LANGUAGE LEARNING ENVIRONMENTS: A POLISH-TURKISH COMPARATIVE STUDY - Gabryś-Barker, Danuta (Neofilolog, 2019)
The term learning environment is a construct perceived by researchers as embracing different aspects of the teaching-learning continuum. It can be described as the physical location where learning occurs: learning in class versus learning beyond it, learning in a home country (with focus on the effects of a learning environment on outcomes of teaching) versus learning abroad (Dewey, 2004, Diaz-Campos, 2004), the latter constituting a fast-growing area of study. Learning environment also means the physical space where formal instruction is carried out (Gabryś-Barker, 2010). But above all, learning environment studies focus on interactions between adults (teachers, parents) and students and show how these relations can affect the latter’s achievement and more generally well-being at school and outside. Thus, it can be seen as mostly affective. This chapter aims to comment on the perceptions pre-service teachers have of a foreign language learning environment, as expressed in their narrative texts on the topic. The data obtained in this study will be compared with the result of a similar study carried out with a group of pre-service EFL teachers in a different cultural setting, in Turkey (Sağlam, Sali, 2013). This should shed some light on whether the trainees’ perceptions are in some way culture-specific and therefore grounded in the educational policies of a given country. The conclusions drawn from the study will hopefully contribute to the ongoing discussion on how to improve FL teachers’ training programmes.